Enriching the interventional vision of cancer with fluorescence and optoacoustic imaging - Garcia-Allende, P. Beatriz; Glatz, Juergen; Koch, Maximilian; Ntziachristos, Vasilis (Journal of Nuclear Medicine, 2013)
Among several techniques considered for surgical and endoscopic imaging, novel optical methods are evolving as a promising approach for interventional guidance. Pilot clinical applications of fluorescence molecular imaging have demonstrated the benefits of using targeted fluorescent agents in cancer surgery. This premise can be extended broadly to interventional guidance through an increasing number of targeted agents and detection techniques. Beyond epi-illumination fluorescence imaging, optoacoustic (photoacoustic) methods are emerging to offer high-resolution cross-sectional optical imaging through several millimeters to centimeters of depth. We present an overview of key recent developments in optical interventional imaging and outline the potential for a paradigm shift in surgical and endoscopic visualization. Copyright © 2013 by the Society of Nuclear Medicine and Molecular Imaging, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Endoscopy; Fluorescence molecular imaging; Fluorescent agents; Optoacoustic imaging; Photoacoustic imaging; Surgery